KONTEKSTUALISASI FOLKLOR TENTANG ARJUNA, KARNA, DAN GATOTKACA KE MEDIA KOMIK DIGITAL NUSANTARA DROID WAR - Nugroho Setiawan, Fredy; Nufiarni, Rizki (JURNAL ILMU BUDAYA, 2023)
This study seeks to reveal folkloric expressions related to Indonesian folklore in a digital comic, Nusantara Droid War. The comic was chosen because it represents Indonesian culture through the presentation of droid characters which are based on folklore, such as Arjuna, Karna, and Gatotkaca which become the objects of this study. Their portrayals are analyzed in terms of folklore process, which is related to how traditional folklore are contextualized with the social and cultural environment in the contemporary era. Therefore, Honko’s premise about folklore life phases is used as a reference to explain the phase where folkloric expression is mediated through digital comics. The results of this study indicate that the folklore of Arjuna, Karna, and Gatotkaca have experienced significant contextualization in their “second phase” of life. Contextualization occurs in the form of recycling the lores of the characters which considers commercial factor and preservation of Indonesian culture.